Polyolefin composition, carpet tile comprising same, and method of making carpet tile
By developing a polyolefin composition containing a specific proportion of acrylic elastomer, a low viscosity acrylic elastomer, alicyclic hydrogenated resin tackifier and filler, the polyolefin backing in a square carpet in the prior art is solved by developing a polyolefin composition containing a specific proportion of acrylic elastomer, a low viscosity acrylic elastomer, alicyclic hydrogenated resin tackifier and filler. The problem of poor performance achieves better mechanical and environmentally friendly performance.
Patent Information
- Application Number
- CN202411589199.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-08
- Publication Date
- 2025-02-18
- Estimated Expiration
- 2044-11-08
AI Technical Summary
Existing thermoplastic polyolefin backings are difficult to achieve a good balance of elasticity, hardness and processing properties in square carpets, while the peeling strength and tufting pull-out force are insufficient.
Developed a polyolefin composition comprising 16-30% of the first acrylic elastomer, 0-10% of the low viscosity second acrylic elastomer, 4-10% of the alicyclic hydrogenated resin tackifier and 50 -80% of the filler is formed by extrusion processing.
Good extrusion flowability, appropriate hardness and mechanical properties of the polyolefin composition are achieved, the peeling strength and tufting pull-out force of the square carpet are improved, and the emission of total volatile organic compounds is reduced.
Smart Images

Figure CN119463363A_ABST
Abstract
Description
Technical Field
[0001] The present disclosure relates to a polyolefin composition, a carpet tile comprising the composition, and a method for preparing the carpet tile. Background Art
[0002] The carpet market is large and growing rapidly, with recyclability and health issues being the focus. In 2023 alone, China's domestic production of carpet tiles will reach about 90 million square meters, with an average compound annual growth rate of 8%. The backing system of carpet tiles is usually based on asphalt and PVC. However, both asphalt and PVC backings face odor problems and are difficult to recycle.
[0003] The demand for sustainable and odorless products has promoted the development of thermoplastic polyolefin backings. However, conventional thermoplastic polyolefin backings have difficulty in achieving a good balance of elasticity, hardness and processing performance, and have insufficient peel strength and tuft pull-out force.
[0004] Therefore, it is necessary to develop a polyolefin composition with good performance to overcome the defects of the prior art. Summary of the invention
[0005] The present disclosure provides a polyolefin composition comprising:
[0006] (i) 16 to 30 weight percent of at least one first propylene-based elastomer, wherein the first propylene-based elastomer has a melt flow rate of 25 to 120 g / 10 min, as measured in accordance with ASTM D1238 at 230° C. under a load of 2.16 kg;
[0007] (ii) 0-10 wt% of at least one low viscosity second propylene-based elastomer, wherein the viscosity of the low viscosity second propylene-based elastomer is 800-2500 mPa·s, as measured at 190° C. in accordance with ASTM D1084-16;
[0008] (iii) 4 to 10 wt. % of at least one tackifier selected from alicyclic hydrogenated resins; and
[0009] (iv) 50-80 wt % of filler;
[0010] In each case, based on the total weight of the polyolefin composition,
[0011] The melt index of the polyolefin composition is 2-10 g / 10 min, 3-8 g / 10 min, or 3.5-6 g / 10 min, or 3.5-4.5 g / 10 min, and the melt index is measured according to ASTM D1238 at a load of 2.16 kg and 190° C.
[0012] Another aspect of the present disclosure provides a carpet tile comprising the polyolefin composition according to the present disclosure.
[0013] Another aspect of the present disclosure provides a method for preparing a tile carpet, which comprises using the polyolefin composition according to the present disclosure as a backing material, for example, forming the backing material by extrusion processing of the polyolefin composition, particularly at a temperature of 170-230°C, or 185-225°C, or 200-220°C.
[0014] The polyolefin composition disclosed in the present invention has good extrusion fluidity, suitable hardness and good mechanical properties. The polyolefin composition disclosed in the present invention is also suitable for preparing the backing material of the square carpet at a high processing temperature, thereby further improving the performance of the carpet. The square carpet prepared using the polyolefin composition has excellent peeling strength and tufting pull-out force, and the method for preparing the square carpet disclosed in the present invention can further improve the performance of the obtained square carpet. BRIEF DESCRIPTION OF THE DRAWINGS
[0015] Figure 1 : LCR (Laboratory Capillary Rheology) viscosity curves of samples 1, 2 and 3. DETAILED DESCRIPTION
[0016] Polyolefin composition
[0017] One aspect of the present disclosure relates to a polyolefin composition comprising:
[0018] (i) 16 to 30 weight percent of at least one first propylene-based elastomer, wherein the first propylene-based elastomer has a melt flow rate of 25 to 120 g / 10 min, as measured in accordance with ASTM D1238 at 230° C. under a load of 2.16 kg;
[0019] (ii) 0-10 wt% of at least one low viscosity second propylene-based elastomer, wherein the viscosity of the low viscosity second propylene-based elastomer is 800-2500 mPa·s, as measured at 190° C. in accordance with ASTM D1084-16;
[0020] (iii) 4 to 10 wt. % of at least one tackifier selected from alicyclic hydrogenated resins; and
[0021] (iv) 50-80 wt % of filler;
[0022] In each case, based on the total weight of the polyolefin composition,
[0023] The melt index of the polyolefin composition is 2-10 g / 10 min, or 3-8 g / 10 min, or 3.5-6 g / 10 min, or 3.5-4.5 g / 10 min, and the melt index is measured according to ASTM D1238 at a load of 2.16 kg and 190° C.
[0024] According to the present disclosure, the melt flow rate of the first propylene-based elastomer is 25-120 g / 10min (e.g., 30 g / 10min, 40 g / 10min, 50 g / 10min, 60 g / 10min, 65 g / 10min, 70 g / 10min, 80 g / 10min, 90 g / 10min, 100 g / 10min, 105 g / 10min, 110 g / 10min or 115 g / 10min), such as 30-110 g / 10min or 35-110 g / 10min, or 30-65 g / 10min or 35-60 g / 10min or 35-55 g / 10min, or 80-120 g / 10min or 80-110 g / 10min or 85-110 g / 10min, and the melt flow rate is in accordance with ASTM D1238, measured at 2.16 kg load and 230°C.
[0025] The first propylene-based elastomer comprises units derived from propylene and units derived from one or more C2 or C4-C 12 In the first propylene-based elastomer, the amount of units derived from propylene is at least 60 wt %, at least 75 wt %, or at least 85 wt %. In one embodiment, the first propylene-based elastomer comprises at least 60 wt %, at least 75 wt %, or at least 85 wt % of units derived from propylene and 3-25 wt % (e.g., 5 wt %, 8 wt %, 10 wt %, 15 wt %, or 20 wt %) or 5-20 wt %, or 8-15 wt % derived from one or more C2 or C4-C 12 The α-olefin may be selected from 1-butene, 1-pentene, 1-hexene, 4-methyl-1-pentene or 1-octene.
[0026] In the first propylene-based elastomer, the elastomer is derived from one or more C2 or C4-C 12 The units of α-olefins may consist essentially of units derived from ethylene, for example units derived from one or more C2 or C4-C 12 At least 95 wt % or at least 98 wt % of the units of the α-olefins are units derived from ethylene. In one embodiment, the units derived from one or more C2 or C4-C 12The units of α-olefins are composed of units derived from ethylene.
[0027] In one embodiment, the first propylene-based elastomer has a weight average molecular weight of 80,000-180,000 g / mol (e.g., 100,000, 120,000, 140,000, 150,000 or 160,000 g / mol), such as 100,000-150,000 g / mol. The molecular weight distribution of the first propylene-based elastomer can be, for example, 1.2-2 or 1.4-1.9.
[0028] The first propylene-based elastomer may be, for example, Vistamaxx available from ExxonMobil TM 6502 and Vistamaxx TM 6902, especially Vistamaxx TM 6502.
[0029] According to the present disclosure, the polyolefin composition comprises 16-30 wt % (e.g., 18 wt %, 20 wt %, 22 wt %, 25 wt % or 28 wt %), such as 20-28 wt %, such as 20-26 wt % of the first propylene-based elastomer, based on the total weight of the polyolefin composition.
[0030] In one embodiment, the propylene-based elastomer has a g / cm 3 (e.g. 0.88 g / cm 3 or 0.90g / cm 3 ) density.
[0031] According to the present disclosure, the polyolefin composition comprises 0-10 wt % (e.g., 1 wt %, 2 wt %, 3 wt %, 4 wt %, 5 wt %, 6 wt %, 7 wt %, 8 wt % or 9 wt %), e.g., 2-8 wt % or 3-6 wt % of the low viscosity second propylene-based elastomer, based on the total weight of the polyolefin composition.
[0032] According to the present disclosure, the viscosity of the low-viscosity second propylene-based elastomer is 800-2500 mPa·s (e.g., 1000, 1200, 1500, 1800, 2000 or 2300 mPa·s), such as 1000-1800 mPa·s or 1000-1500 mPa·s, and the viscosity is measured at 190° C. according to ASTM D1084-16.
[0033] The low viscosity second propylene-based elastomer comprises units derived from propylene and units derived from one or more C2 or C4-C 12In the second low viscosity propylene-based elastomer, the amount of units derived from propylene is at least 80 wt% or at least 90 wt%. In one embodiment, the second low viscosity propylene-based elastomer comprises at least 80 wt% or at least 90 wt% of units derived from propylene and 3-20 wt% (e.g., 5 wt%, 8 wt%, 10 wt%, 15 wt%, or 18 wt%) or 4-10 wt% of units derived from one or more C2 or C4-C 12 The α-olefin may be selected from 1-butene, 1-pentene, 1-hexene, 4-methyl-1-pentene or 1-octene.
[0034] In the low-viscosity second propylene-based elastomer, the elastomer is derived from one or more C2 or C4-C 12 The units of α-olefins may consist essentially of units derived from ethylene, for example units derived from one or more C2 or C4-C 12 At least 95 wt % or at least 98 wt % of the units of the α-olefins are units derived from ethylene. In one embodiment, the units derived from one or more C2 or C4-C 12 The units of α-olefins are composed of units derived from ethylene.
[0035] The molecular weight of the second low-viscosity propylene-based elastomer may be 20,000-60,000 g / mol (eg, 30,000 g / mol, 40,000 g / mol, or 50,000 g / mol).
[0036] According to the present disclosure, the polyolefin composition comprises 4-10 wt % (e.g., 5 wt %, 6 wt %, 7 wt %, 8 or 9 wt %), such as 4-8 wt % of at least one tackifier selected from alicyclic hydrogenated resins, based on the total weight of the polyolefin composition.
[0037] The viscosity of the alicyclic hydrogenated resin used as a tackifier may be 500-1500 mPa·s (eg, 600 mPa·s, 800 mPa·s, 1000 mPa·s, or 1200 mPa·s), or 600-1200 mPa·s, as measured at 160° C. according to ASTM D1084-16.
[0038] An example of the alicyclic hydrogenated resin can be Escorez available from ExxonMobil TM 5400.
[0039] According to the present disclosure, the polyolefin composition comprises 50-80 wt % (e.g., 55 wt %, 60 wt %, 65 wt %, 68 wt %, 70 wt %, 72 wt %, 75 wt % or 78 wt %), such as 55-75 wt % or 60-75 wt % filler. The filler can be selected from calcium carbonate, magnesium hydroxide and aluminum hydroxide, especially calcium carbonate.
[0040] The filler may be in powder form. The particle size of the filler may be 200-1000 mesh (such as 300 mesh, 400 mesh, 500 mesh, 600 mesh, 700 mesh, 800 mesh or 900 mesh), for example 300-800 mesh.
[0041] In one embodiment, the polyolefin composition may further include at least one compatibilizer. Compatibilizers include, for example, functionalized polyolefins. For example, in one embodiment, the functionalized polyolefin is a maleated polyolefin, such as maleated polyethylene, maleated polypropylene, maleated elastomers based on ethylene or propylene. In one embodiment, the compatibilizer is a maleated high density polyethylene. The maleated polyolefin may have at least 0.1 wt %, such as at least 0.5 wt % or at least 1 wt %, such as a maleic anhydride grafting level of 0.5-1.5 wt %. An example of the maleated polyethylene as a compatibilizer is Exxelor 1040 that can be purchased from TCC.
[0042] In one embodiment, the amount of the compatibilizer can be 0-8 wt % (e.g., 0.5 wt %, 1 wt %, 1.5 wt %, 2 wt %, 3 wt %, 4 wt %, 5 wt %, 6 wt %, 7 wt %), such as 0.5-8 wt %, or 1-5 wt %, based on the total weight of the polyolefin composition.
[0043] In one embodiment, the polyolefin composition comprises:
[0044] (i) 16 to 28 weight percent of at least one first propylene-based elastomer, wherein the first propylene-based elastomer has a melt flow rate of 30 to 110 g / 10 min, as measured in accordance with ASTM D1238 at 230° C. under a load of 2.16 kg;
[0045] (ii) 0-10 wt% of at least one low viscosity second propylene-based elastomer, wherein the viscosity of the low viscosity second propylene-based elastomer is 800-2500 mPa·s, as measured at 190° C. in accordance with ASTM D1084-16;
[0046] (iii) 4 to 10 wt. % of at least one tackifier selected from alicyclic hydrogenated resins; and
[0047] (iv) 55-75% by weight of filler;
[0048] In each case, based on the total weight of the polyolefin composition,
[0049] The melt index of the polyolefin composition is 2-10 g / 10 min, or 3-8 g / 10 min, or 3.5-6 g / 10 min, or 3.5-4.5 g / 10 min, and the melt index is measured according to ASTM D1238 at a load of 2.16 kg and 190° C.
[0050] In one embodiment, the polyolefin composition comprises:
[0051] (i) 16 to 28 weight percent of at least one first propylene-based elastomer, wherein the first propylene-based elastomer has a melt flow rate of 80 to 110 g / 10 min, as measured in accordance with ASTM D1238 at 230° C. under a load of 2.16 kg;
[0052] (ii) 0-5 wt% of at least one low viscosity second propylene-based elastomer, wherein the viscosity of the low viscosity second propylene-based elastomer is 800-2500 mPa·s, as measured at 190° C. in accordance with ASTM D1084-16;
[0053] (iii) 4 to 10 wt. % of at least one tackifier selected from alicyclic hydrogenated resins; and
[0054] (iv) 60-75 wt % filler;
[0055] In each case, based on the total weight of the polyolefin composition,
[0056] The melt index of the polyolefin composition is 3-8 g / 10 min, or 3.5-6 g / 10 min, or 3.5-4.5 g / 10 min, and the melt index is measured according to ASTM D1238 at a load of 2.16 kg and 190° C.
[0057] In one embodiment, the polyolefin composition comprises:
[0058] (i) 16 to 28 weight percent of at least one first propylene-based elastomer, wherein the first propylene-based elastomer has a melt flow rate of 30 to 65 g / 10 min, as measured in accordance with ASTM D1238 at 230° C. under a load of 2.16 kg;
[0059] (ii) 2 to 8 weight percent of at least one low viscosity second propylene-based elastomer, wherein the viscosity of the low viscosity second propylene-based elastomer is 800 to 2500 mPa·s, as measured at 190° C. in accordance with ASTM D1084-16;
[0060] (iii) 4 to 10 wt. % of at least one tackifier selected from alicyclic hydrogenated resins; and
[0061] (iv) 60-75 wt % filler;
[0062] In each case, based on the total weight of the polyolefin composition,
[0063] The melt index of the polyolefin composition is 3-8 g / 10 min, or 3.5-6 g / 10 min, or 3.5-4.5 g / 10 min, and the melt index is measured according to ASTM D1238 at a load of 2.16 kg and 190° C.
[0064] In one embodiment, the polyolefin composition comprises:
[0065] (i) 16 to 28 weight percent of at least one first propylene-based elastomer, wherein the first propylene-based elastomer has a melt flow rate of 30 to 65 g / 10 min, as measured in accordance with ASTM D1238 at 230° C. under a load of 2.16 kg;
[0066] (ii) 2 to 8 weight percent of at least one low viscosity second propylene-based elastomer, wherein the viscosity of the low viscosity second propylene-based elastomer is 800 to 2500 mPa·s, as measured at 190° C. in accordance with ASTM D1084-16;
[0067] (iii) 4 to 10% by weight of at least one tackifier selected from alicyclic hydrogenated resins;
[0068] (iv) 60-75 wt. % filler; and
[0069] (v) 1-5 wt % of a compatibilizer;
[0070] In each case, based on the total weight of the polyolefin composition,
[0071] The melt index of the polyolefin composition is 3-8 g / 10 min, or 3.5-6 g / 10 min, or 3.5-4.5 g / 10 min, and the melt index is measured according to ASTM D1238 at a load of 2.16 kg and 190° C.
[0072] In one embodiment, the polyolefin composition comprises:
[0073] (i) 16 to 28 weight percent of at least one first propylene-based elastomer, wherein the first propylene-based elastomer has a melt flow rate of 30 to 65 g / 10 min, as measured in accordance with ASTM D1238 at 230° C. under a load of 2.16 kg; the first propylene-based elastomer comprising at least 85 weight percent of units derived from propylene and 8 to 15 weight percent of units derived from ethylene;
[0074] (ii) 2 to 8 weight percent of at least one low viscosity second propylene-based elastomer, wherein the viscosity of the low viscosity second propylene-based elastomer is 1000 to 1800 mPa·s, as measured at 190° C. in accordance with ASTM D1084-16;
[0075] (iii) 4 to 10% by weight of at least one tackifier selected from alicyclic hydrogenated resins;
[0076] (iv) 60-75 wt. % filler; and
[0077] (v) 1-5 wt % of a compatibilizer;
[0078] In each case, based on the total weight of the polyolefin composition,
[0079] The melt index of the polyolefin composition is 3.5-6 g / 10 min, or 3.5-4.5 g / 10 min, and the melt index is measured according to ASTM D1238 at a load of 2.16 kg and 190° C.
[0080] In one embodiment, the polyolefin composition comprises:
[0081] (i) 16 to 28 weight percent of at least one first propylene-based elastomer, wherein the first propylene-based elastomer has a melt flow rate of 35 to 60 g / 10 min, as measured in accordance with ASTM D1238 at 230° C. under a load of 2.16 kg; the first propylene-based elastomer comprising at least 85 weight percent of units derived from propylene and 8 to 15 weight percent of units derived from ethylene;
[0082] (ii) 3 to 6 weight percent of at least one low viscosity second propylene-based elastomer, wherein the viscosity of the low viscosity second propylene-based elastomer is 1000 to 1800 mPa·s, as measured at 190° C. in accordance with ASTM D1084-16;
[0083] (iii) 4 to 8 weight percent of at least one tackifier selected from alicyclic hydrogenated resins;
[0084] (iv) 60-75 wt. % calcium carbonate; and
[0085] (v) 1-5 wt% of a compatibilizer, wherein the compatibilizer is a maleated polyolefin;
[0086] In each case, based on the total weight of the polyolefin composition,
[0087] The melt index of the polyolefin composition is 3.5-4.5 g / 10 min, and the melt index is measured according to ASTM D1238 at a load of 2.16 kg and 190° C.
[0088] The polyolefin composition of the present disclosure may have a flexural modulus of 70-180 MPa, or 90-160 MPa, or 100-160 MPa, or 120-150 MPa, as measured in accordance with ASTM D790.
[0089] The polyolefin composition of the present disclosure may have a tensile yield stress of 2-5 MPa, or 2.5-4.5 MPa, or 3.5-4.5 MPa, as measured in accordance with ASTM D638.
[0090] The polyolefin composition of the present disclosure may have a Shore hardness of A80-95 and / or D20-38, the Shore hardness being measured according to ASTM D2240.
[0091] Carpet tile and method for preparing carpet tile
[0092] One aspect of the present disclosure relates to a carpet tile comprising the polyolefin composition according to the present invention.
[0093] In one embodiment, the polyolefin composition is used as a backing material, for example, the polyolefin composition is formed into a backing material by extrusion, especially at a temperature of 170-230°C (e.g., 175°C, 180°C, 185°C, 190°C, 195°C, 200°C, 205°C, 210°C, 215°C, 220°C or 225°C), or 185-225°C, or 200-220°C.
[0094] In one embodiment, the carpet comprises an upper carpet surface and a lower base layer in addition to the backing material, that is, the backing material is located between the upper carpet surface and the lower base layer.
[0095] In one embodiment, the backing material is obtained by extrusion processing of the following polyolefin composition at a temperature of 200-220° C., the polyolefin composition comprising:
[0096] (i) 16 to 28 weight percent of at least one first propylene-based elastomer, wherein the first propylene-based elastomer has a melt flow rate of 35 to 60 g / 10 min, as measured in accordance with ASTM D1238 at 230° C. under a load of 2.16 kg; the first propylene-based elastomer comprising at least 85 weight percent of units derived from propylene and 8 to 15 weight percent of units derived from ethylene;
[0097] (ii) 3 to 6 weight percent of at least one low viscosity second propylene-based elastomer, wherein the viscosity of the low viscosity second propylene-based elastomer is 1000 to 1800 mPa·s, as measured at 190° C. in accordance with ASTM D1084-16;
[0098] (iii) 4 to 8 weight percent of at least one tackifier selected from alicyclic hydrogenated resins;
[0099] (iv) 60-75 wt. % calcium carbonate; and
[0100] (v) 1-5 wt% of a compatibilizer, wherein the compatibilizer is a maleated polyolefin;
[0101] In each case, based on the total weight of the polyolefin composition,
[0102] The melt index of the polyolefin composition is 3.5-4.5 g / 10 min, and the melt index is measured according to ASTM D1238 at a load of 2.16 kg and 190° C.
[0103] The transverse peel strength of the carpet tile comprising the polyolefin composition of the present invention can be 30-100N (e.g., 35, 40, 50, 60, 70, 80, 85, 90 or 95N), for example, 50-100N, for example, 85-95N, and / or the transverse peel strength can be 18-100N (e.g., 20, 25, 30, 40, 50, 60, 70, 80, 85, 90 or 95N), for example, 25-100N, for example, 50-100N, for example, 80-95N, and the peel strength is measured according to GB-T 11746-2008.
[0104] The tuft pull-out force of the carpet tile comprising the polyolefin composition of the present disclosure may be 50-60N, tested according to QB / T2755-2005.
[0105] The TVOC of the carpet tile containing the polyolefin composition of the present disclosure does not exceed 0.025 mg / (m 2 ·h), if not exceeding 0.02mg / (m 2 h), tested in accordance with GB 18587-2001.
[0106] One aspect of the present disclosure relates to a method for preparing a carpet tile, comprising using the polyolefin composition of the present disclosure as a backing material, for example, forming the backing material by extrusion processing the polyolefin composition, in particular, extrusion processing is carried out at a temperature of 170-230°C (e.g., 175°C, 180°C, 185°C, 190°C, 195°C, 200°C, 205°C, 210°C, 215°C, 220°C or 225°C), or 185-225°C, or 200-220°C.
[0107] The backing material is typically in the form of a backing sheet.
[0108] Usually, after the extrusion process, the backing material is compounded with the upper carpet surface and the lower base layer, for example, after the extrusion process, the backing material is compounded with the upper carpet surface and the lower base layer without cooling.
[0109] The polyolefin composition of the present disclosure allows processing at high extrusion processing temperatures, and the resulting carpet tiles have excellent peel strength.
[0110] In one embodiment, the method for preparing a carpet tile of the present disclosure comprises extruding the following polyolefin composition at a temperature of 200-220° C. to obtain a backing material, wherein the polyolefin composition comprises:
[0111] (i) 16 to 28 weight percent of at least one first propylene-based elastomer, wherein the first propylene-based elastomer has a melt flow rate of 35 to 60 g / 10 min, as measured in accordance with ASTM D1238 at 230° C. under a load of 2.16 kg; the first propylene-based elastomer comprising at least 85 weight percent of units derived from propylene and 8 to 15 weight percent of units derived from ethylene;
[0112] (ii) 3 to 6 weight percent of at least one low viscosity second propylene-based elastomer, wherein the viscosity of the low viscosity second propylene-based elastomer is 1000 to 1800 mPa·s, as measured at 190° C. in accordance with ASTM D1084-16;
[0113] (iii) 4 to 8 weight percent of at least one tackifier selected from alicyclic hydrogenated resins;
[0114] (iv) 60-75 wt. % calcium carbonate; and
[0115] (v) 1-5 wt% of a compatibilizer, wherein the compatibilizer is a maleated polyolefin;
[0116] In each case, based on the total weight of the polyolefin composition,
[0117] The melt index of the polyolefin composition is 3.5-4.5 g / 10 min, and the melt index is measured according to ASTM D1238 at a load of 2.16 kg and 190° C.
[0118] Those skilled in the art can more easily understand the present invention according to the following embodiments:
[0119] 1. A polyolefin composition comprising:
[0120] (i) 16 to 30 weight percent of at least one first propylene-based elastomer, wherein the first propylene-based elastomer has a melt flow rate of 25 to 120 g / 10 min, as measured in accordance with ASTM D1238 at 230° C. under a load of 2.16 kg;
[0121] (ii) 0-10 wt% of at least one low viscosity second propylene-based elastomer, wherein the viscosity of the low viscosity second propylene-based elastomer is 800-2500 mPa·s, as measured at 190° C. in accordance with ASTM D1084-16;
[0122] (iii) 4 to 10 wt. % of at least one tackifier selected from alicyclic hydrogenated resins; and
[0123] (iv) 50-80 wt % of filler;
[0124] In each case, based on the total weight of the polyolefin composition,
[0125] The melt index of the polyolefin composition is 2-10 g / 10 min, or 3-8 g / 10 min, or 3.5-6 g / 10 min, or 3.5-4.5 g / 10 min, and the melt index is measured according to ASTM D1238 at a load of 2.16 kg and 190° C.
[0126] 2. The polyolefin composition according to embodiment 1, wherein the melt flow rate of the first propylene-based elastomer is 30-110 g / 10 min, or 30-65 g / 10 min, or 80-110 g / 10 min, and the melt flow rate is measured according to ASTM D1238 at a load of 2.16 kg and 230°C.
[0127] 3. The polyolefin composition according to embodiment 1 or 2, wherein the first propylene-based elastomer comprises units derived from propylene and units derived from one or more C2 or C4-C 12The first propylene-based elastomer comprises at least 60 wt % or at least 75 wt % or at least 85 wt % of units derived from propylene and 3-25 wt % or 5-20 wt % or 8-15 wt % of units derived from one or more C2 or C4-C 12 α-olefin units.
[0128] 4. The polyolefin composition according to any one of embodiments 1 to 3, wherein the polyolefin composition comprises 16 to 28 wt% of the first propylene-based elastomer, based on the total weight of the polyolefin composition.
[0129] 5. The polyolefin composition according to any one of embodiments 1 to 4, wherein the polyolefin composition comprises 2-8 wt%, or 3-6 wt% of the low viscosity second propylene-based elastomer, based on the total weight of the polyolefin composition.
[0130] 6. The polyolefin composition according to any one of embodiments 1 to 5, wherein the viscosity of the low viscosity second propylene-based elastomer is 1000-1800 mPa·s, as measured at 190° C. according to ASTM D1084-16.
[0131] 7. The polyolefin composition according to any one of embodiments 1 to 6, wherein the low viscosity second propylene-based elastomer comprises units derived from propylene and units derived from one or more C2 or C4-C 12 The low viscosity second propylene-based elastomer comprises at least 80 wt % or at least 90 wt % of units derived from propylene and 3-20 wt % or 4-10 wt % of units derived from one or more C2 or C4-C 12 α-olefin units.
[0132] 8. The polyolefin composition according to any one of embodiments 1 to 7, wherein the amount of the tackifier selected from alicyclic hydrogenated resins is 4 to 8 wt %, based on the total weight of the polyolefin composition.
[0133] 9. The polyolefin composition according to any one of embodiments 1 to 8, wherein the filler is selected from calcium carbonate, magnesium hydroxide and aluminum hydroxide, and / or the particle size of the filler is 200-1000 mesh, such as 300-800 mesh, and / or the amount of the filler is 55-75 wt%.
[0134] 10. The polyolefin composition according to any of embodiments 1 to 9, wherein the polyolefin composition further comprises at least one compatibilizer, for example a functionalized polyolefin, such as a maleated polyolefin.
[0135] 11. The polyolefin composition according to embodiment 10, wherein the amount of the compatibilizer is 0.5-8 wt%, or 1-5 wt%, based on the total weight of the polyolefin composition.
[0136] 12. A polyolefin composition comprising:
[0137] (i) 16 to 28 weight percent of at least one first propylene-based elastomer, wherein the first propylene-based elastomer has a melt flow rate of 35 to 60 g / 10 min, as measured in accordance with ASTM D1238 at 230° C. under a load of 2.16 kg; the first propylene-based elastomer comprising at least 85 weight percent of units derived from propylene and 8 to 15 weight percent of units derived from ethylene;
[0138] (ii) 3 to 6 weight percent of at least one low viscosity second propylene-based elastomer, wherein the viscosity of the low viscosity second propylene-based elastomer is 1000 to 1800 mPa·s, as measured at 190° C. in accordance with ASTM D1084-16;
[0139] (iii) 4 to 8 weight percent of at least one tackifier selected from alicyclic hydrogenated resins;
[0140] (iv) 60-75 wt. % calcium carbonate; and
[0141] (v) 1-5 wt% of a compatibilizer, wherein the compatibilizer is a maleated polyolefin;
[0142] In each case, based on the total weight of the polyolefin composition,
[0143] The melt index of the polyolefin composition is 3.5-4.5 g / 10 min, and the melt index is measured according to ASTM D1238 at a load of 2.16 kg and 190° C.
[0144] 13. A carpet tile comprising the polyolefin composition according to any one of embodiments 1 to 12.
[0145] 14. The carpet tile according to embodiment 13, wherein the polyolefin composition is used as a backing material, for example, the polyolefin composition is formed into a backing material by extrusion, in particular at a temperature of 170-230°C, or 185-225°C, or 200-220°C.
[0146] 15. A method for preparing a carpet tile, comprising using the polyolefin composition according to any one of embodiments 1 to 12 as a backing material, for example, forming the backing material by extrusion processing of the polyolefin composition, in particular at a temperature of 170-230°C, or 185-225°C, or 200-220°C.
[0147] 16. The method according to embodiment 15, comprising the step of laminating the backing material with an upper carpet surface and a lower base layer.
[0148] Example
[0149] The following examples are provided to illustrate but not to limit the present invention. Unless otherwise specified, the amount of each substance in the examples is based on weight.
[0150] raw material
[0151] Vistamaxx TM 6502 (hereinafter referred to as VM6502): propylene-ethylene copolymer elastomer, available from ExxonMobil, containing about 13% by weight of ethylene comonomer, with a viscosity of about 0.865 g / cm 3 A density of about 45 g / 10 min and a melt flow rate of about 45 g / 10 min as measured at 230° C. under a load of 2.16 kg in accordance with ASTM D1238;
[0152] Vistamaxx TM 6902 (hereinafter referred to as VM6902): propylene-ethylene copolymer elastomer, available from ExxonMobil, containing about 12% by weight of ethylene comonomer, with a viscosity of about 0.869 g / cm 3 A density of about 100 g / 10 min and a melt flow rate measured at 230° C. under a load of 2.16 kg in accordance with ASTM D1238;
[0153] Vistamaxx TM 8880 (hereinafter referred to as VM8880): propylene-ethylene copolymer elastomer, available from ExxonMobil, containing about 6 wt% ethylene comonomer, and having a viscosity of 1200 mPa·s, as measured at 190° C. according to ASTM D1084-16.
[0154] Escorez TM 5400 (hereinafter referred to as Escorez 5400): a cycloaliphatic hydrogenated resin, available from ExxonMobil, with a viscosity of 800 mPa·s, which is measured at 160° C. according to ASTM D1084-16.
[0155] Exxelor 1040: maleic anhydride grafted high density polyethylene, available from TCC.
[0156] Calcium carbonate powder: 400 mesh.
[0157] Methods and standards
[0158] Melt index (MI): ASTM D1238;
[0159] LCR (Laboratory Capillary Rheology) Viscosity: ASTM D3835;
[0160] Flexural modulus: ASTM D790;
[0161] Tensile stress: ASTM D638;
[0162] Shore hardness: ASTM D2240;
[0163] Peel strength: GB-T 11746-2008;
[0164] Tufting pull-out force: QB / T 2755-2005;
[0165] Total volatile organic compounds (TVOC): GB 18587-2001.
[0166] Example 1: Preparation of polyolefin composition samples 1-3
[0167] Preparation of mixed particles: Samples 1-3 were all prepared into cylindrical mixed particles using a twin-screw extruder with a screw diameter of 40 mm. Taking sample 1 as an example, first, 21% of VM6502, 4.5% of VM8880 and 4.5% of Escorez 5400 other than calcium carbonate powder were dry-mixed in a planetary mixer, and the dry-mixed particles obtained after being uniformly mixed were used for standby. The twin-screw extruder has two feed ports, and the above-mentioned dry-mixed particles enter the barrel from feed port 1, and 35% of calcium carbonate powder is added to feed port 1 at the same time. The temperature in the barrel is set to 150°C, 160°C, 170°C, 180°C, and 200°C, respectively. After the melt extrusion is stable, the remaining 35% of calcium carbonate powder is added from feed port 2. The extruder has an extrusion rate of about 50 kg / h. After the melt extrusion at the die is stable, the underwater pelletizer is attached to the die, and the circulating cooling water is turned on at the same time. The mixed particle product is obtained through the cyclone separator. The preparation process of samples 2 and 3 is similar to that of sample 1, and the formula can be adjusted according to the weight ratio in Table 1 below. The MI and LCR viscosity of samples 1, 2 and 3 are shown in Table 2, and the mechanical properties and Shore hardness are shown in Table 3.
[0168] Table 1
[0169]
[0170] Table 2
[0171]
[0172] The LCR viscosity curves of samples 1, 2 and 3 are shown in Figure 1 , at low shear rates (10s -1 ), from top to bottom are sample 2, sample 1 and sample 3.
[0173] As shown in Table 2, the MI of all samples 1-3 is between 4 and 6, which can be processed by extrusion process. Figure 1 The LCR viscosity in Table 2 shows that at low shear rates, the viscosity of sample 2 is higher than that of samples 1 and 3, while the difference is smaller at high shear rates. -1 At a low shear rate, sample 2 has the highest viscosity of 462.1 Pa·s, which can provide higher melt strength during extrusion and thus have better processing performance.
[0174] Table 3
[0175]
[0176] Table 3 shows that Sample 2 has the highest stiffness and hardness. Sample 3 shows lower stiffness and hardness.
[0177] Example 2: Carpet backing extrusion and carpet surface lamination to prepare carpet tiles
[0178] The samples prepared in Example 1 are respectively used as the backing raw materials for processing the square carpet. The extruded backing sheet (middle layer) is compounded with the carpet surface (upper layer) and the polypropylene non-woven fabric layer (lower layer) at high temperature through an extrusion compounding machine, and cooled to room temperature through a cooling roller, thereby obtaining the final carpet product. The extrusion processing temperature of the backing sheet is 180-210°C (as shown in Table 4), the cooling roller temperature is 30°C, and the line speed of the extrusion compounding machine is 10m / min. Sample 1 has a low melt strength and cannot be extruded into a backing sheet at 190°C and above, while Sample 2 can be extruded into a backing sheet at 190°C and above, so Sample 2 has better processing performance.
[0179] The peel strength of the carpets obtained using samples 1 and 2 is shown in Table 4, and the tuft pull-out force and TVOC are shown in Table 5.
[0180] Table 4
[0181] Longitudinal peel strength (N) Transverse peel strength (N) Sample 1 (180°C backside processing temperature) 33.2 19.4 Sample 2 (190°C backside processing temperature) 54.1 29.1 Sample 2 (210°C backside processing temperature) 88.3 95.1
[0182] Table 4 shows that the carpet processed by the samples of the present invention has good transverse and longitudinal peeling strength, wherein the carpet obtained by using sample 2 shows higher peeling strength than the carpet obtained by using sample 1. In addition, the comparison between the carpets processed by using sample 2 at 190°C and 210°C shows that a higher backing sheet extrusion processing temperature is helpful to improve the peeling strength, which is particularly beneficial for carpet processing on an extrusion production line.
[0183] Table 5
[0184] Tufting pull-out force (N) <![CDATA[TVOC / (mg / (m 2 ·h))]]> Sample 1 (180°C processing temperature) 54.5 0.017 Sample 2 (190°C processing temperature) 53.7 0.021 Commercially available PVC-based carpet 44.9 0.047 Commercially available asphalt-based carpet 39.6 0.065
[0185] As can be seen from Table 5, the tuft pull-out force of the carpets processed from samples 1 and 2 is higher than that of commercially available carpets. In addition, the TVOC of the carpets processed from samples 1 and 2 is significantly lower.
[0186] Although the present invention is disclosed as above with preferred embodiments, the present invention is not limited thereto. Any changes and modifications made by any person skilled in the art without departing from the spirit and scope of the present invention should be included in the protection scope of the present invention, so the protection scope of the present invention should be based on the scope defined by the claims.
Claims
1. A polyolefin composition comprising: (i) 16 to 30 weight percent of at least one first propylene-based elastomer, wherein the first propylene-based elastomer has a melt flow rate of 25 to 120 g / 10 min, as measured in accordance with ASTM D1238 at 230° C. under a load of 2.16 kg; (ii) 0-10 wt% of at least one low viscosity second propylene-based elastomer, wherein the viscosity of the low viscosity second propylene-based elastomer is 800-2500 mPa·s, as measured at 190° C. in accordance with ASTM D1084-16; (iii) 4 to 10 wt. % of at least one tackifier selected from alicyclic hydrogenated resins; and (iv) 50-80 wt % of filler; In each case, based on the total weight of the polyolefin composition, The melt index of the polyolefin composition is 2-10 g / 10 min, or 3-8 g / 10 min, or 3.5-6 g / 10 min, or 3.5-4.5 g / 10 min, and the melt index is measured according to ASTM D1238 at a load of 2.16 kg and 190° C.
2. The polyolefin composition according to claim 1, wherein the melt flow rate of the first propylene-based elastomer is 30-110 g / 10 min, or 30-65 g / 10 min, or 80-110 g / 10 min, and the melt flow rate is measured according to ASTM D1238 at a load of 2.16 kg and 230°C.
3. The polyolefin composition according to claim 1 or 2, wherein the first propylene-based elastomer comprises units derived from propylene and units derived from one or more C2 or C4-C 12 The first propylene-based elastomer comprises at least 60 wt % or at least 75 wt % or at least 85 wt % of units derived from propylene and 3-25 wt % or 5-20 wt % or 8-15 wt % of units derived from one or more C2 or C4-C 12 α-olefin units.
4. The polyolefin composition according to any one of claims 1 to 3, wherein the polyolefin composition comprises 16 to 28 wt% of the first propylene-based elastomer, based on the total weight of the polyolefin composition.
5. The polyolefin composition according to any one of claims 1 to 4, wherein the polyolefin composition comprises 2 to 8 wt%, or 3 to 6 wt% of the low viscosity second propylene-based elastomer, based on the total weight of the polyolefin composition.
6. The polyolefin composition according to any one of claims 1 to 5, wherein the viscosity of the low viscosity second propylene-based elastomer is 1000 to 1800 mPa·s, the viscosity being measured at 190°C according to ASTM D1084-16.
7. The polyolefin composition according to any one of claims 1 to 6, wherein the low viscosity second propylene-based elastomer comprises units derived from propylene and units derived from one or more C2 or C4-C 12 The low viscosity second propylene-based elastomer comprises at least 80 wt % or at least 90 wt % of units derived from propylene and 3-20 wt % or 4-10 wt % of units derived from one or more C2 or C4-C 12 α-olefin units.
8. The polyolefin composition according to any one of claims 1 to 7, wherein the amount of the tackifier selected from alicyclic hydrogenated resins is 4 to 8% by weight, based on the total weight of the polyolefin composition.
9. The polyolefin composition according to any one of claims 1 to 8, wherein the filler is selected from calcium carbonate, magnesium hydroxide and aluminum hydroxide, and / or the particle size of the filler is 200-1000 mesh, such as 300-800 mesh, and / or the amount of the filler is 55-75 wt%.
10. The polyolefin composition according to any one of claims 1 to 9, wherein the polyolefin composition further comprises at least one compatibilizer, such as a functionalized polyolefin, such as a maleated polyolefin.
11. The polyolefin composition according to claim 10, wherein the amount of the compatibilizer is 0.5-8 wt%, or 1-5 wt%, based on the total weight of the polyolefin composition.
12. A polyolefin composition comprising: (i) 16 to 28 weight percent of at least one first propylene-based elastomer, wherein the first propylene-based elastomer has a melt flow rate of 35 to 60 g / 10 min, as measured in accordance with ASTM D1238 at 230° C. under a load of 2.16 kg; the first propylene-based elastomer comprising at least 85 weight percent of units derived from propylene and 8 to 15 weight percent of units derived from ethylene; (ii) 3 to 6 weight percent of at least one low viscosity second propylene-based elastomer, wherein the viscosity of the low viscosity second propylene-based elastomer is 1000 to 1800 mPa·s, as measured at 190° C. in accordance with ASTM D1084-16; (iii) 4 to 8 weight percent of at least one tackifier selected from alicyclic hydrogenated resins; (iv) 60-75 wt. % calcium carbonate; and (v) 1-5 wt% of a compatibilizer, wherein the compatibilizer is a maleated polyolefin; In each case, based on the total weight of the polyolefin composition, The melt index of the polyolefin composition is 3.5-4.5 g / 10 min, and the melt index is measured according to ASTM D1238 at a load of 2.16 kg and 190° C.
13. A carpet tile comprising the polyolefin composition according to any one of claims 1 to 12.
14. The carpet tile according to claim 13, wherein the polyolefin composition is used as a backing material, for example, the polyolefin composition is formed into a backing material by extrusion, in particular at a temperature of 170-230°C, or 185-225°C, or 200-220°C.
15. A method for preparing a carpet tile, comprising using the polyolefin composition according to any one of claims 1 to 12 as a backing material, for example, forming the backing material by extrusion processing of the polyolefin composition, in particular, extrusion processing is carried out at a temperature of 170-230°C, or 185-225°C, or 200-220°C, for example, the method comprises the step of compounding the backing material with an upper carpet surface and a lower base layer.
Citation Information
Patent Citations
Carpet backing layer composition
CN110869552A
Olefin-based polymer compositions for flooring applications
CN112639008A
Ultra-soft polyolefin composition
CN116406384A
Propylene-based blend composition
CN118434803A
Hot melt adhesive composition
CN118525067A
